2009
DOI: 10.1007/s00464-009-0422-6
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic gallstones after sleeve gastrectomy

Abstract: There was no significant difference in symptomatic or complicated gallstone disease between the patients treated with laparoscopic SG and those treated with laparoscopic RYGBP. Routine prophylactic cholecystectomy should not be recommended for weight reduction during laparoscopic SG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 26 publications
3
33
0
2
Order By: Relevance
“…In our study we found 5.8 % of sleeve patients and 6.4 % of LRYGB patients, already had their gallbladder removed or had gallstone disease before the operation. This result is similar to that of other studies (16,18). Portenier et al (14) argued that the incidence of delayed cholecystectomy for symptoms or complications of gallstone formation was much lower than the ≥30% reported to develop gallstones and suggested an expectant approach of the asymptomatic cholelithiasis in LRYGB patients.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…In our study we found 5.8 % of sleeve patients and 6.4 % of LRYGB patients, already had their gallbladder removed or had gallstone disease before the operation. This result is similar to that of other studies (16,18). Portenier et al (14) argued that the incidence of delayed cholecystectomy for symptoms or complications of gallstone formation was much lower than the ≥30% reported to develop gallstones and suggested an expectant approach of the asymptomatic cholelithiasis in LRYGB patients.…”
supporting
confidence: 88%
“…Of our LRYGB group, 9.7 % developed symptomatic cholelithiasis and underwent laparoscopic cholecystectomy, this result is the same in many studies done by Nagem et al (15)and Li et al (16) which reported a rate ranged from 6.7 to 11.8%, theoretically, cholelithiasis is less common after laparoscopic sleeve gastrectomy, because the procedure does not alter the gastrointestinal pathway (16,17).…”
supporting
confidence: 81%
“…Many studies reported up to 15-25 % incidence 5 years after gastric surgery [1][2][3][4][5][6] with a mean value estimated of 17 % in all studies [1][2][3][4][5][6][7]. Without a specific evidence in the literature, some authors [4,11] recommend to perform a prophylactic cholecystectomy at the time of gastric surgery, while others do not [1,7] and the decision of gallbladder management is left, to date, to each surgeon's preference.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported a three-four fold increased incidence 5 years after gastric surgery (up to 15-25 %) [1][2][3][4][5][6] with an estimated mean value of 17 % in all studies [1][2][3][4][5][6][7]. The underlying mechanism was thought to be related to surgical dissection of the vagus nerve branches and the anatomical gastrointestinal reconstruction [5,[8][9][10], and to the extent of gastrectomy and lymphadenectomy [1,4,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Some specialists suggest performing routine cholecystectomy at the time of gastric bypass, especially considering the technical difficulties in performing endoscopic retrograde cholangiopancreatography after RYGB [44]. However, most surgeons perform cholecystectomy only if the patient is symptomatic [45]. A possible approach is administration of ursodeoxycholic acid (UDA) post-operatively.…”
Section: Management Of Hepatobiliary Complicationsmentioning
confidence: 99%